Medical Versus Surgical Management for Emphysematous Pancreatic Necrosis: Is Gas Within Pancreatic Necrosis an Absolute Indication for Surgery?. Issue 5 (July 2015) - Barreda, Luis; Targarona, Javier; Pando, Elizabeth; Reynel, Miguel; Portugal, Jose; Barreda, Claudia
Abstract : Objectives: The aim of this study was to evaluate whether pancreatic necrosis with presence of gas is an absolute indication for surgery or if there is a possibility for the medical management of this pathology. Methods: This study is a retrospective study including 56 patients with diagnosis of pancreatic necrosis and gas on computed tomography from April 2003 to March 2011. We recorded all the factors related to each group of treatment, including APACHE II score, C-reactive protein level, Tomographic Severity Index, organ and multiorgan failure, and infected necrosis after fine-needle puncture, to evaluate the differences between surgical and medical treatment. Results: Thirty-six (64%) of these patients were submitted to surgery, whereas 20 (36%) were managed conservatively. Twenty-eight patients (78%) who underwent surgery had infected necrosis. Thirty-five percent of the patients (7 patients) in the medical group had organ failure versus 83% of the patients in the surgical group. Conclusions: Pancreatic necrosis with gas on computed tomography is a relative indication for surgery. Medical management is a feasible and safe possibility for this pathology in selected cases. The presence of organ failure and infected necrosis often precludes a surgical treatment.